Beyond the Blood Sacrifice: Literary Explorations of Latin American Mestizo Culture - Jaeck, Lois Marie (CIENCIA ergo-sum, 2017)
The thought-provoking vision of blood sacrifice as the common ground of pre-Columbian American and European Judeo-Christian societies is reflected in two opposed views of Spain's conquest and colonization of the "New World": Bartolomé de las Casas 'Historia de las Indias and Bernal Díaz del Castillo's Historia Verdadera de la Conquista de la Nueva España. . Nowithstanding the bloody conflicts between the Spaniards and the pre-Columbian aboriginal people, their meeting engendered a Mestizo population, composed of people of "mixed blood", which constitutes a positive affirmation of the common ground shared by European and pre-Columbian cultures. The almost metaphor-like emergence of a Latin American Mestizo culture as a new distinct society is explored in Latin American literature, from the time of the Spanish Conquest until the twentieth century.